IMPLEMENTASI SAPTA PESONA DI TAMAN BALEKAMBANG SURAKARTA - Bartolomeus Herawan Mintardjo (Nawasena: Jurnal Ilmiah Pariwisata, 2022)
Surakarta or commonly known as the city of Solo has an amazing variety of tourist destinations. One of them is Balekang Park. Balekambang Park has an interesting development history and has a large enough area to make it a catchment and lung of the city of Surakarta. In the implementation of tourism activities, it is certainly not good if you miss one of the important concepts, namely Sapta. Sapta pesona itself consists of 7 elements, namely safe, clean, orderly, cool, beautiful, suave, and memorable. With the realization of all existing elements, it will certainly have a positive impact on managers and tourists for the sustainability of tourism activities in the long term.